2021
DOI: 10.1371/journal.pone.0249785
|View full text |Cite
|
Sign up to set email alerts
|

Influenza vaccination uptake and factors influencing vaccination decision among patients with chronic kidney or liver disease

Abstract: Introduction Seasonal influenza is a major global health problem causing substantial morbidity and health care costs. Yet, in many countries, the rates of influenza vaccination remain low. Chronic kidney or liver diseases (CKLD) predispose patients to severe influenza infections, but data on vaccination acceptance and status is limited in this risk population. We investigated the influenza vaccination awareness considering sociodemographic factors in CKLD patients. Patients and methods This cross-sectional, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…Additionally, the multivariate models demonstrate that vaccination compliance increases with age and is strongly associated with having received a previous influenza vaccine shot. A 2021 study on liver transplant patients further supported the association between flu shot uptake and previous influenza vaccination history, reporting an aOR of 20 (95% CI = 8–52) ( 11 ). This finding is consistent with several other studies in the literature that also demonstrate this association among various high-risk subgroups ( 12 , 13 ).…”
Section: Discussionmentioning
confidence: 96%
“…Additionally, the multivariate models demonstrate that vaccination compliance increases with age and is strongly associated with having received a previous influenza vaccine shot. A 2021 study on liver transplant patients further supported the association between flu shot uptake and previous influenza vaccination history, reporting an aOR of 20 (95% CI = 8–52) ( 11 ). This finding is consistent with several other studies in the literature that also demonstrate this association among various high-risk subgroups ( 12 , 13 ).…”
Section: Discussionmentioning
confidence: 96%
“…There are different results in the literature about influenza vaccination rates among ESRD patients. A recent study showed that the influenza vaccination rate for the previous year was 24% among 95 hemodialysis patients (16). 62.5% of these patients thought that they were in the high-risk group for influenza infection (16).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that the influenza vaccination rate for the previous year was 24% among 95 hemodialysis patients (16). 62.5% of these patients thought that they were in the high-risk group for influenza infection (16). This result may be affected by various factors rather than the lack of awareness for immunization.…”
Section: Discussionmentioning
confidence: 99%
“…Seasonal influenza is a worldwide health problem causing morbidity and mortality in CKD. In a study conducted by Eder et al (12) showed that 43.9% of patients for influenza vaccine declared their willingness to be vaccinated in the winter season and the reasons for not planning vaccination were fear of graft injury (33.3%), complications after vaccination (32.4%) and vaccine inefficiency (15.0%). Varicella (chickenpox) is a primary infectious disease that is caused by varicella-zoster virus (VZV), an alpha herpes virus belonging to the Herpesviridae family.…”
Section: Discussionmentioning
confidence: 99%